2004
DOI: 10.1111/j.0022-4367.2004.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Florida's Pension Election: From DB to DC and Back

Abstract: During the year 2002, the State of Florida's 600,000 public employees were given the choice of converting their traditional defined benefit (DB) pension plan into an individual-account defined contribution (DC) plan with full control over asset allocation and investment decisions. To mitigate some of the risk and uncertainty in the decision, the State granted each employee electing the DC plan an additional option to switch back (i.e., change their mind once) at any point prior to retirement. This option has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Media reports by Walsh (2011), Lyman and Walsh (2014), and Greenhouse (2011), among others, have reported on changes in public pension benefit and contribution parameters in the wake of the financial and economic crisis. In the academic literature, Chingos and West (2013), Lachance, Mitchell, and Smetters (2003), and Milevsky, Promislow, and David (2004) examined specific state pension reforms and their impacts on funding and costs. 6 More recently, Novy-Marx and Rauh (2015) have suggested that linking public pension payouts to investment performance could alleviate the critical funding shortfalls many states now face.…”
Section: Relevant Prior Studiesmentioning
confidence: 99%
“…Media reports by Walsh (2011), Lyman and Walsh (2014), and Greenhouse (2011), among others, have reported on changes in public pension benefit and contribution parameters in the wake of the financial and economic crisis. In the academic literature, Chingos and West (2013), Lachance, Mitchell, and Smetters (2003), and Milevsky, Promislow, and David (2004) examined specific state pension reforms and their impacts on funding and costs. 6 More recently, Novy-Marx and Rauh (2015) have suggested that linking public pension payouts to investment performance could alleviate the critical funding shortfalls many states now face.…”
Section: Relevant Prior Studiesmentioning
confidence: 99%
“…More recently, Samwick and Skinner (2004) characterize the distribution of pension benefits for DB and DC schemes by simulating a broad range of earnings paths, portfolio composition, and portfolio returns for several different individuals, and McCarthy (2003) compares DC and DB plans in the context of a life‐cycle model. Lachance, Mitchell, and Smetters (2003) and Milevsky and Promislow (2004) compare DB and DC plans, when DC plan participants have an option to buy back their DB benefit for a price. Blake, Cairns, and Dowd (2007) present simulation results for the likely pension outcomes for different DC pension plan members distinguished by occupation and gender.…”
Section: Introductionmentioning
confidence: 99%
“… Although this is not the focus on our paper, a number of states and public sector employers in the United States have recently taken similar steps of freezing or partially converting their DB pensions into DC plans. See the papers by Milevsky and Promislow (2004) and Lachance, Mitchell, and Smetters (2003) for a discussion of this trend and some of the financial economic issues involved. …”
mentioning
confidence: 99%